2015
DOI: 10.7314/apjcp.2015.16.17.7859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Agent Gemcitabine and Docetaxel in Second-Line Therapy for Advanced Stage Non-Small Cell Lung Cancer in a University Hospital in Turkey

Abstract: Purpose: To compare the efficacy and toxicity of gemcitabine versus docetaxel in a second-line setting of nonsmall cell lung cancer (NSCLC) patients previously treated with platin-based combination chemotherapy. Materials and Methods: We retrospectively evaluated the medical records of 57 patients treated with single agent gemcitabine or docetaxel in second-line setting of advanced NSCLC who received one prior platinumbased therapy. Results: The mean age was 56.7±8.39 years with 55 ( 96.5%) males and two (3.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
“…Some of the studies that describe the efficacy of non-platinum-based and combination therapy as second-line treatment regimens are described in Table 4. The MST of docetaxel and gemcitabine are 21 and 22 months, respectively, when used as monotherapies [21]. Docetaxel, though considered to be a gold-standard for the second-line treatment of NSCLC, gemcitabine shows equal potential that can be studied further as an alternative to docetaxel.…”
Section: Discussionmentioning
confidence: 99%